What We Can Learn From Covid 19 Pandemic: A Zoom Lens From Islamic Viewpoint Based On Hadith - Mughaneswari Sahadevan; Siti Mardhiyah Kamal Azhar; Nur Izzati Liyana Azizan; Nor Azura A Rahman (UNIVERSITI SULTAN ZAINAL ABIDIN, 2024)
MALAYSIAN JOURNAL FOR ISLAMIC STUDIES Volume 6 No.2 Page (63-72)